Основні суперечності сучасної етнонаціональної політики Азербайджану - Вітман, Костянтин Миколайович; Витман, Константин Николаевич; Vitman, К. (My University, 2012)
The modern period’s characteristics of Azerbaijan Republic ethnonational policy are studied. The closest attention is paid to key collisions of the protection of national minorities rights on the offi cial and practical level of ethnonational policy of the state.
Вітман К. М. Основні суперечності сучасної етнонаціональної політики Азербайджану / К. М. Вітман // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 201-209.
Keywords: формування етнонаціональної політики Азербайджану; суперечності забезпечення прав національних меншин на офіційному рівні; суперечності забезпечення прав національних меншин на практичному рівні; етнонаціональна політика зарубіжних країн; формирование этнонациональной политики Азербайджана; противоречия обеспечения прав национальных меньшинств на официальном уровне; противоречия обеспечения прав национальных меньшинств на практическом уровне; этнонациональная политика зарубежных стран; the formation of ethnic policy of Azerbaijan; conflicts of rights of national minorities at the official level; conflicts of rights of national minorities at the practical level; ethno-national policy of foreign countries